Formation of the youth’s social memory in the Eurasian integration states-participants - G. I. Osadchaya (RUDN journal of Sociology, 2021)
In the past thirty years, social memory of the Eurasian youth has been influenced by many actors of the commerative space, who often pursue their own goals in the struggle to legitimize the new political order and their policies of the radical economic transformation. The results of their efforts should be taken into account in the implementation of one of the most important joint projects of the post-Soviet countries - Eurasian integration, because social memory of the youth is the most important resource for its success. The study aims at clarifying and evaluating the mechanisms for preserving information about the past, the peculiarities of the generation Y ideas about the common history and the current stage of the EAEU construction, which are present in the public discourse, and at revealing the relationship between attitudes to the past and to the Eurasian integration, the influence of social memory on the personal worldview, the forms and methods of its reconstruction in the interests of the post-Soviet countries interaction and efficiency of the politics of memory. The formation of social memory is defined as the activity of actors (individuals, groups, organizations, social institutions, communities) aimed at the interpretation of the collective past and common present by the youth of the countries participating in the Eurasian integration. The empirical object of the study - young citizens of the member states and candidates for joining the EAEU (18-38 years old), who live, study or work in Moscow. The article considers the respondents assessments of the contribution of each of the actors to the social memory formation and describes social memory of the generation Y as a set of views, feelings and moods reflecting the perception of the Soviet past and the common present. The authors insist on the purposeful policy of the leaders of the countries, participating in the Eurasian integration, to ensure the reconstruction of the youths social memory and the consolidation of societies.